24 JUNE 2018 PRESIDENTIAL ELECTION CANDIDATES PARTICIPATING OF TURKEY IN PRE-ELECTION CAMPAIGN METHOD POLITICAL PARTY OR PERSONAL WEB SITE WITH INVESTIGATION CONTENT USING SOCIAL MEDIA MARKETING ANALYSIS - Ruhan İRİ (Fırat University, 2020)
This study, the scope of political marketing evaluated in the framework of promotional efforts and marketing communications with political marketing activities they perform in the pre-election campaign of the participating presidential candidate in the presidential election held across the country on June 24, 2018 in the framework of the transition period for the first time made and the presidential system in Turkey, personal or party web The use of social media and social media is analyzed by content analysis method. Between the dates of June 01-24, 2018, the results of the content analysis were evaluated in accordance with the data and information obtained as a result of evaluations of the presidential candidates on their personal or party websites as well as their facebook, twitter and instagram accounts. Research is important in terms of not working in this field before and shedding light on the researches that can be done in this area in the future. The research universe of this study consists of 6 presidential candidates participating in the elections on 24 June 2018 with photos, videos, slogans and all kinds of verbal shares on their personal or party websites and facebook, twitter, instagram accounts. The data were evaluated according to the complete counting method. Some descriptive statistics were used to evaluate the data. As a result of the study, it was found out that the presidential candidates Muharrem İNCE and Meral AKŞENER were using their personal or party website and social media accounts as twitter, instagram and facebook pages more actively, intensively and effectively in terms of their political marketing activities and promotion tools than other candidates. In addition, all of the presidential candidates participating in the election, personal or party website and social media accounts, twitter, instagram and facebook pages are mostly rally photos in political marketing activities, selfie photos and self-advertisement / posters / announcements / announcements Because of the publication of all the rally videos, it was observed that personal or party website and social media accounts were used as a virtual rally area.